PENGEMBANGAN RESTFUL API UNTUK MEMBANTU PEMBUDIDAYA IKAN LELE DALAM SISTEM MANAJEMEN RANTAI PASOK “PANEN-PANEN” - Yunhasnawa, Yoppy; Aprilianto, Salies; Allam, Muhammad Faiq; Himawan, Dhimas Arbi Sukma (Jurnal Cahaya Mandalika ISSN 2721-4796 (online), 2023)
Food is a necessity that cannot be eliminated in life in this world. Food is one of the benchmarks for a country whether the country is prosperous or not in meeting the food needs of its citizens. The category of food that Indonesian people really like is catfish. The high market demand for catfish has resulted in catfish cultivators being overwhelmed in meeting these food needs. One effort that can be done is to initiate the design of a "Harvest-Harvest" supply chain management system, which consists of 3 different platforms, namely cultivators/farmers, feed providers, and marketplaces. The system designed in this development is based on Service REST API. Through the Rapid Application Development (RAD) development methodology, all parties who took part in the development of the "Harvest-Harvest" supply chain management system, including designers, programmers, partners, and users who have been identified, take part in the role until all features are complete and running well as should.